NCOA4-Mediated Ferritinophagy: A Vicious Culprit in COVID-19 Pathogenesis? - Jia, Fengju; Liu, Hongxia; Kang, Shan (Frontiers in Molecular Biosciences, 2021)
Coronavirus disease 2019 (COVID-19) is a global pandemic that has caused widespread loss of life. Notably, in this disease, severe inflammatory reactions characterized by cytokine storms are caused by severe acute respiratory syndrome coronavirus 2. The cytokine storms may promote hyper-ferritinemia which can further intensify the inflammation. Moreover, elevated ferritin levels trigger nuclear receptor coactivator 4 (NCOA4)-mediated ferritinophagy, in which ferritin is degraded and iron is released. Excess iron released from ferritinophagy can promote ferroptosis and cellular damage. Therefore, we propose that NCOA4-mediated ferritinophagy can be targeted to limit the ferroptosis and prevent the multi-organ damage and severity in COVID-19 patients.